Risk factors of early adverse events associated with endoscopic ultrasound-guided hepaticogastrostomy using self-expandable metal stent - Nakaji, So; Takahashi, Hirokazu; Yoshioka, Wataru; Shiratori, Toshiyasu; Yoshimura, Shigenobu; Kawamitsu, Natsuki; Tomonari, Akiko (Endoscopy International Open, 2024)
Background and study aims This retrospective study aimed to investigate risk factors for early adverse events (AEs) associated with endoscopic ultrasonography-guided hepaticogastrostomy (EUS-HGS) using self-expandable metal stents (SEMS).Patients and methods The clinical success rate, technical success rate, and early AEs were assessed at two hospitals from 2010 to 2022. The analysis focused on risk factors associated with cholangitis, peritonitis, and SEMS migration.Results Technical success was achieved in all cases (94/94), and clinical success was 96.8% (91/94). Post-procedural acute cholangitis occurred in 12.8%of cases (12/94). However, no statistically significant risk factors were identified for cholangitis or biliary tract infection. Peritonitis occurred in only 2.1% of cases (2/94). Univariate analysis, using a 1.5 cm cut-off for the distance between the liver and gastrointestinal tract, revealed significant risk factors: braided-type SEMS, bile duct diameter (especially >4 mm), 6 mm diameter SEMS, and tract dilation (P=0.001, P=0.020, P=0.023, and P=0.046, respectively). Adjusting the cut-offs to 2 cm underscored braided-type SEMS and tract dilation as risk factors (P=0.002 and P=0.046, respectively). With 2.5-cm cut-offs, only braided-type SEMS remained significant (P=0.018). Mortality within 14 and 30 days following EUS-HGS was 5.3% (5/94) and 16.0% (15/94), respectively.Conclusions EUS-HGS using SEMS demonstrated high technical and clinical success rates. Laser-cut SEMS may be superior in preventing early AEs.
Keywords: Biliary tract; Intervention EUS; Endoscopic ultrasonography; Pancreas